Mass Transfer Coefficient During Cathodic Protection of Low Carbon Steel in Seawater - Hameed, Khalid W.; Khadom, Anees Abdullah; Rahman, Ameel Mohammed (Al-Khwarizmi Engineering Journal, 2009)
The aim of this research is to calculate mass transfer coefficient, kd, during cathodic protection of low carbon steel in neutral seawater (3.5% W/V NaCl in distilled water with pH = 7). Two types of cathodic protection were used: First: Sacrificial anode cathodic protection (SACP) were a pipeline of steel carrying seawater using zinc as a sacrificial anode and with variable temperatures ranged (0 – 45oC) and volumetric flow rate ranged (5 – 900 lit/hr). It was found that the kd increases with increasing temperature and volumetric flow rate of seawater, where kd ranged (0.24×10-6 – 41.6×10-6 m/s). Second: Impressed current cathodic protection (ICCP) technique adopting a rotating vertical steel cylinder in seawater with variable temperatures ranged (0 – 45oC) and rotating velocity ranged (0 – 400 rpm). It was found that the kd increases with increasing temperature and rotating velocity, where kd ranged (7.25×10-6 – 36.82×10-6 m/s).